(3x-5)=0

Simple and best practice solution for (3x-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-5)=0 equation:


Simplifying
(3x + -5) = 0

Reorder the terms:
(-5 + 3x) = 0

Remove parenthesis around (-5 + 3x)
-5 + 3x = 0

Solving
-5 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 3x = 0 + 5

Combine like terms: -5 + 5 = 0
0 + 3x = 0 + 5
3x = 0 + 5

Combine like terms: 0 + 5 = 5
3x = 5

Divide each side by '3'.
x = 1.666666667

Simplifying
x = 1.666666667

See similar equations:

| N+.5n=63 | | 0.7x+0.5=0.9x-0.7 | | 8(x+3)=4x+5 | | 3(y+7)=2(y+8) | | 6x+4=32 | | 2x-10-8=24-16-8x | | .143(49-7y)=14 | | -5(2-5x)+(-8x-2)=-4x-8x | | 6b=348 | | 15x/7=11/7 | | 3m-9x-1=24 | | 5-(.5)g=12 | | 5(4x-7)+13x-20=8(x+10)-15x+65 | | 15x/7=0 | | -[8z-(18z+3)]=3+(9z+10) | | 11x+2=10x+4 | | 92=2h | | X*1+2*0.6=2+X*0.9 | | 2c^2-c-6= | | -196=-9.8x^2 | | 9p+2=4+8p | | 2x+1=-(9) | | 6x^2-23x=7 | | 5k=50 | | 2(3r-6)-(2r+1)=-13 | | q=p(r+s)p | | x^2(x^2-64)-25(x^2-64)=0 | | 2x^2-22x+60=0 | | x+6+x=46 | | -8+3x-2-6x=17 | | F(9)=3(9)+2 | | 7n=16.1 |

Equations solver categories